A logistic process immaturity model proposal - Mateo Márquez-Gutiérrez; Guillermo Carmona-Gonzalez; Carlos Castro-Zuluaga (Foundations of Management, 2020)
Aims: To develop an immaturity model for the assessment of logistic processes that can assess the practices that describe the level of criticality, which maturity models do not evaluate, of these processes. Originality: Application of the little-known variation of maturity models and immaturity models in business logistic processes. Research method: The research is conducted from a literature review primarily with terms such as immaturity models and process immaturity. As literature is poor, it is supported by the maturity models developed by various authors in multiple domains. Main findings: Asa result, an immaturity model is obtained for the assessment of the main logistic processes of manufacturing companies. Likewise, the evaluation and the experiences collected from its application in acompany of a case study are obtained. Implications for theory and practice: The studies about immaturity of processes are few. The model is designed for manufacturing companies whose logistics management differs from service companies.
Keywords: L23; L60; M11; 650; immaturity model; logistic processes; process assessment; criticality; business management